Pembangunan Sistem Informasi Praktik Pengalaman Lapangan Pendidikan Teknologi Informasi (Studi Pada Prodi PTI FILKOM UB Malang) - Achmad Marzuki; Satrio Agung Wicaksono; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Pedagogic competence main requirement is to be possessed a teachers. On the study education information technology, the faculty computer science brawijaya university obliged to take lecture practices experience (PPL) any college student with have qualified, requirements to reduce lulusannya became a staff having competence pedagogic. In the registration process PPL needed time until six days to be registered in the implementation of the PPL. Day This study attempts to develop information systems which was able to help in the registration process for the ppl related parties that students can use a PPL the registration. This study attempts to develop information systems can help in the registration process ppls for the associated the students can do the PPL use the registration. Information systems that will have to be made 7 functional needs systems and 1 needs non-fungsional system 1. methods development information systems used which is the prototype evolutionary. And then design system. Then the next done system systems to through the testing of using black box testing virtue of testing in each case the show results 100% valid system. And then done testing the simulation time analysis before the registration process the ppl done manually takes time 6 day on the basis of the process business, as-is if the registration process the ppl use systems takes time rata-rata 27 47 minutes seconds, show in terms of time more eficien and can help to every college student when the PPL registration.